Investigation of a Highly Pathogenic Avian Influenza Outbreak in a Poultry Farm, Dhamrai, Bangladesh, 2017: a One Health Approach - Islam, Sirazul; Billah, Mallick Masum; Islam, Kazi Munisul; Afreen, Nawroz; Shirin, Tahmina; Flora, Meerjady Sabrina (Outbreak, Surveillance, Investigation & Response (OSIR) Journal, 2021)
In January 2017, a highly pathogenic avian influenza (HPAI) A virus killed 732 chickens in a farm in Dhamrai, Bangladesh. An investigation assessed transmission of the virus from chickens to farmworkers. Contacts were farmworkers with direct exposure to affected chickens. We interviewed all suspected cases, conducted an active case finding for human cases at the implicated farm and local clinics, and actively searched for carcasses of wild and domestic birds within two kilometers of the implicated farm. All contacts were asymptomatic and had buried dead poultry; 70% touched dead poultry and 29% used protective gloves while working. Nasal and throat swabs were negative for influenza A and B viruses (subtyped for M-gene positive influenza A viruses by PCR and seasonal H3, H1N1 pdm09, and avian H5/H7/H9). The virus was probably introduced to the farm when ducks from the farm were taken to a live bird market and unsold ducks were returned to the farm. While farmworkers were exposed to the infected chickens, there was no evidence of the virus being transmitted to workers. We recommend starting H5N1 surveillance in live bird markets to monitor HPAI.